Investigation on the genetic-inconsistent paternity cases using the MiSeq FGx system - Anqi Chen; Ruiyang Tao; Chengtao Li; Suhua Zhang (Oxford University Press, 2022)
Mutations might challenge the paternity index calculation in forensic identification. While many studies have focussed on the autosomal short tandem repeats (A-STR), the mutation status of sex chromosomes and single nucleotide polymorphism (SNP) remain blank. Next generation sequencing (NGS), known as high throughput and large sequence polymorphism, is a promising tool for forensic genetics. To describe the mutation landscapes in the paternity cases with genetic inconsistencies, a total of 63 parentage confirmed paternity cases contained at least one mismatched locus have been collected. The mutations were subsequently evaluated using Verogen's MPS ForenSeqTM DNA Signature Kit and a microsatellite instability (MSI) detection kit. The result showed 98.41% (62/63) of the cases had no additional autosomal mutations even when the number of A-STRs increased to 27. As for the sex chromosomes, about 11.11% (7/63) of the cases exhibited either X-STR or Y-STR mutations. D2S1338, FGA and Penta E were the most frequent altered STRs, which suggested they might be the mutation hotspots. In addition, a male with sex chromosome abnormality was observed accidently, whose genotype might be 47, XXY, rather than MSI. Nearly 56.90% of the STR loci possessed isoalleles, which might result in higher STR polymorphisms. No Mendelian incompatibility was detected among the SNP markers, which indicated that SNP was a more reliable genetic marker in the genetic-inconsistent paternity cases.Supplemental data for this article is available online at https://doi.org/10.1080/20961790.2021.2009631 .